2010
DOI: 10.1080/09297049.2010.485980
|View full text |Cite
|
Sign up to set email alerts
|

Association between Inhibitory Control Capacity and Body Weight in Overweight and Obese Children and Adolescents: Dependence on Age and Inhibitory Control Component

Abstract: It has been assumed that overweight individuals show weak inhibitory control capacity leading to a failure to resist external cues for palatable food and that this deficit underlies the recently reported empirical association between obesity and attention deficit/hyperactivity disorder (ADHD). In childhood and adolescence, empirical research on this issue is scarce. Here, the hypothesis is tested that high body weight is associated with weak inhibitory control performance and that this association is moderated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
68
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(75 citation statements)
references
References 34 publications
6
68
0
1
Order By: Relevance
“…Obese children have been found to exhibit heightened reward sensitivity, decreased inhibitory control, and increased impulsivity when compared to children of normal weight. A recent study examining inhibitory control in children suggested that high impulsivity was linked with obesity (31). Impulsivity and reward sensitivity have specifically been found to influence BMI through overeating (32) and high levels of impulsivity may be associated with a rebound effect after eating (7).…”
Section: Discussionmentioning
confidence: 99%
“…Obese children have been found to exhibit heightened reward sensitivity, decreased inhibitory control, and increased impulsivity when compared to children of normal weight. A recent study examining inhibitory control in children suggested that high impulsivity was linked with obesity (31). Impulsivity and reward sensitivity have specifically been found to influence BMI through overeating (32) and high levels of impulsivity may be associated with a rebound effect after eating (7).…”
Section: Discussionmentioning
confidence: 99%
“…Using the Go/No-Go and incompatibility tasks of the Attention Assessment Battery ( n = 177) in 8- to 15-year-old children, Pauli-Pott et al . 17 reported a link between high impulsivity and higher BMI in younger participants. Cserjési et al .…”
Section: Introductionmentioning
confidence: 98%
“…In the search to identify critical and modifiable child-level factors that contribute to overweight/obesity risk, executive control (EC) – a set of “top-down” cognitive processes for directing attention and behavior (Garon, Bryson, & Smith, 2008) – has been proposed as a potentially important construct for study (e.g., Martin & Davidson, 2014). An emerging literature suggests a link between poor EC (also known as “executive function”) and overweight/obesity in pediatric samples (e.g., Anzman & Birch, 2009; Pauli-Pott, Albayrak, Hebebrand, & Pott, 2010; Reinert, Po’e, & Barkin, 2013); however, important limitations in existing research undermine our understanding of this association. First, much of the research in this are a is cross-sectional, precluding any insight into the directionality of effects.…”
mentioning
confidence: 99%